(untitled) (Journal of Education and Development, 2020)
Individuals are both more likely to participate in sports, exercise, and physical activity when they are skilled. Therefore, motor skills and skilled movement should be viewed as prerequisites to a physically active lifestyle. Children and adolescents who have achieved fundamental motor competence are also believed to perceive themselves as being competent although there is inconsistency in the results so far reported in the literature. Despite the unprecedented growth home homeschool education, studies have not examined the development of motor competency of homeschool students or its relationship to confidence. The current investigation examined the influence fundamental motor skill development and self-confidence of students enrolled in a university homeschool physical education program. Results from the pre-test (M = 13.92, SD = 2.8) and post-test (M =